Spatio-temporal dynamics of beached asbestos cement wastes colonized by terrestrial and shallow marine organisms: new insights and environmental implications - Giacobbe, Salvatore; Somma, Roberta (Frontiers in Earth Science, 2025)
Investigations carried out on the geological/ecological asset of Peloro Cape, northeastern Sicily (Italy), revealed the presence of hundreds of asbestos cement material (ACM) fragments, whose features indicated their origin from undulated roofing sheets left in demolition waste dumps, later exposed to marine coastal erosion. Some fragments showed clear evidence of biotic activity, both in the form of corrosion and encrustation. The first stage of colonization was indicated by organic weathering under subaerial conditions, evidenced by bare substrates left by lichens. A second stage of colonization was recognized through the calcareous remains of marine encrusting organisms found in shallow marine environments. In this latter phase, evidence of biotic overgrowth of spirorbids, large serpulids, oysters, bryozoans, and vermetid gastropods indicated a successional process likely developed over a timespan of several decades. Repeated phases of immersion and stranding due to storms, however, may also be considered. Subaerial and subaqueous colonization may be indirectly tied, since lichen may contribute to make inert Asbestos materials, facilitating the later settlement of marine encrusting biota. The combined action of continental and marine biota thus reduces the release of hazardous asbestos fibers into the environment. Such a process, nevertheless, cannot affect the smallest fragments, which are too unstable on the sea bottom to be colonized. In conclusion, multiple interferences from uncontrolled ACM waste have affected both emerged and submerged coastal environments. These impacts need to be evaluated, particularly with regard to their threat to human health. Areas affected by environmental and health risks due to asbestos exposure should be remediated to avoid damage to humans, living organisms, and ecosystems, whose relationships in marine environments have been almost neglected. This research addresses the knowledge gap regarding the sources and fate of hazardous ACM waste after being transferred and transported by alluvial and marine waters. It may support competent public authorities and technicians in planning real remediation activities once the full complexity of the coastal area contamination is understood.